Integration Redesign for The Multifunctional Building-Abd Al Naser Saad Al Deen Shakaa in Nablus - ندى قشوع; مريم عورتاني; ابراهيم حسن (My University, 2023)
Multifunctional building is a structure that contains at least two different destination spaces, it allows to use the urban space in a more efficient and compact way. A multifunctional building in Nablus was selected as our graduation project. This project should cover architectural, structural and environmental aspects, in addition to earthquake resistance. The project aims to assess the architectural, structural and environmental aspects of the multifunctional building according to code requirements and considerations. In addition to analysing the site in terms of public safety and emergency exits, and ensuring the readiness of the building in the event of a fire. The structural design involves constructing a 3D model for all blocks in the project and the seismic load will be taken into account in the design. The project is also a quantitative survey to estimate the budget of the building. Initially, the building was studied ecologically by analysing the site and accordingly environmental problems in terms of ventilation, solar radiation and shadows were addressed. Then the architectural aspect was studied and improved. An additional parking floor for cars was added to suit the number of students in the residences, and an emergency staircase was added, in addition to changing some room sizes based on the criteria and adding some facilities to the building. Then the structural aspect was studied and adjustments were made to the column sites. The building is under construction now, but there are a lot of similar buildings available inPalestin.